Cultural Literacy in Elementary School Students: A Systematic Study on Character Building - Dwi Mahmud Rizki Riyanto; Rachmat Setiawan; Anindya Syam Choudhury (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aims to comprehensively review how cultural literacy is applied in elementary schools and its impact on the character development of students. The research method chosen for this study is the Systematic Literature Review method. Data collection was conducted by documenting and reviewing all articles related to cultural literacy in elementary schools published between 2016 - 2025 and published in Scopus-indexed journals. The articles used in the study were identified and selected based on criteria for analysis. The selection process resulted in five articles that were reviewed in depth through content analysis. The main findings of this study are classified into three dimensions: (1) the relevance of cultural literacy in the era of globalization, (2) the integration of local wisdom into education, and (3) the role of educators and learning strategies. These three dimensions indicate that cultural literacy helps students understand more about cultural diversity, strengthen their character, and enhance their national identity. This study emphasizes and recommends that cultural literacy-based learning should be implemented systematically and contextually, starting from the elementary school level.